MEMAKNAI ZAKAT PROFESI DAN PERHITUNGANNYA - Komala Dewi; Fauziah nur Hutauruk; Yadi Islami (CV. Armas Suan Sejahtera, 2024)
Zakat is a mandatory worship for all Muslims who are financially able and have reached the minimum limit for paying zakat or called nisab. Zakat is a certain portion of wealth that must be paid by every Muslim if they have met the specified requirements. As one of the pillars of Islam, Zakat is paid to be given to groups who are entitled to receive it (asnaf). In terms of language, zakat means clean (cleansing oneself), holy (purifying oneself), blessing and growing. Zakat comes from the word